From Sidney to OLGA: an overview of atrophic gastritis - Crafa, Pellegrino; Russo, Michele; Miraglia, Chiara; Barchi, Alberto; Moccia, Florenzo; Nouvenne, Antonio; Leandro, Gioacchino; Meschi, Tiziana; de' Angelis, Gian Luigi; Di Mario, Francesco (Acta Biomedica Atenei Parmensis, 2018)
Chronic gastritis is a long-lasting disease that can lead to a loss of appropriate gastric glands. Gastritis, as term, apply to an inflammation of the stomach, histologically proven, sometimes with structural mucosal changes. Worldwide Helicobacter pylori’s infection play a pivotal role as the main etiological effector of chronic active gastritis. H. p. is a bacterium with a selective tropism for the gastric mucosa, able to survive in a hostile environment for colonization of organisms other than itself, able to develop strategies for survival and for avoidance of the defence mechanisms, causing inflammatory changes, that vary from asymptomatic mild gastritis to more severe injury such as peptic ulcer as well as premalignant lesions and malignant tumours. The pattern and distribution of gastritis strongly correlate with these sequelae and chronic atrophic gastritis with intestinal metaplasia is now assessed as a precancerous lesion with definite risk of evolution towards intraepithelial lesions of both low and high grade, as expected in the model of the Correa’s cascade. In fact, the leading complication of chronic gastritis remains its close correlation with gastric cancer being biologically linked to H. pylori infection, nowadays known as a class I carcinogen. Gastric carcinogenesis is due to environmental factors, as well as to bacterial strain, host responses and gastric mucosal microbiome dysbiosis. Since, individual patients show different gastric cancer risk, it is mandatory to identify patients at risk of developing gastric cancer to offer a targeted search for lesions with a more rapid development of neoplasm liable, in an early phase, to a less destructive treatment. OLGA staging system is the most reliable and powerful system that allow the recognition of patient with a higher risk of developing gastric cancer.